Circulating anti-Müllerian hormone and breast cancer risk: A study in ten prospective cohorts - Ge, W; Clendenen, TV; Afanasyeva, Y; Koenig, KL; Agnoli, C; Brinton, LA; Dorgan, JF; Eliassen, AH; Falk, RT; Hallmans, G; Hankinson, SE; Hoffman-Bolton, J; et al. (Wiley, 2018)
A strong positive association has been observed between circulating anti-Müllerian hormone (AMH), a biomarker of ovarian reserve, and breast cancer risk in three prospective studies. Confirming this association is important because of the paucity of biomarkers of breast cancer risk in premenopausal women. We conducted a consortium study including ten prospective cohorts that had collected blood from premenopausal women. A nested case-control design was implemented within each cohort. A total of 2,835 invasive (80%) and in situ (20%) breast cancer cases were individually matched to controls (n = 3,122) on age at blood donation. AMH was measured using a high sensitivity enzyme-linked immunoabsorbent assay. Conditional logistic regression was applied to the aggregated dataset. There was a statistically significant trend of increasing breast cancer risk with increasing AMH concentration (ptrend across quartiles < 0.0001) after adjusting for breast cancer risk factors. The odds ratio (OR) for breast cancer in the top versus bottom quartile of AMH was 1.60 (95% CI = 1.31-1.94). Though the test for interaction was not statistically significant (pinteraction = 0.15), the trend was statistically significant only for tumors positive for both estrogen receptor (ER) and progesterone receptor (PR): ER+/PR+: ORQ4-Q1 = 1.96, 95% CI = 1.46-2.64, ptrend <0.0001; ER+/PR-: ORQ4-Q1 = 0.82, 95% CI = 0.40-1.68, ptrend = 0.51; ER-/PR+: ORQ4-Q1 = 3.23, 95% CI =0.48-21.9, ptrend = 0.26; ER-/PR-: ORQ4-Q1 = 1.15, 95% CI = 0.63-2.09, ptrend = 0.60. The association was observed for both pre- (ORQ4-Q1= 1.35, 95% CI= 1.05-1.73) and post-menopausal (ORQ4-Q1 =1.61, 95% CI = 1.03 - 2.53) breast cancer (pinteraction = 0.34). In this large consortium study, we confirmed that AMH is associated with breast cancer risk, with a 60% increase in risk for women in the top vs. bottom quartile of AMH.